Biochemical treatment of wastewater from canning companies for biogas and digestate production - Bublienko, Natalia; Salavor, Oksana; Nychyk, Oksana; Stetsenko, Natalia (My University, 2024)
Canneries are a powerful source of wastewater. Wastewater is produced at various stages of the technological process and is contaminated with carbohydrates, proteins, fats, etc. Often, such wastewater is not treated or discharged into natural reservoirs incompletely treated. It is advisable to use methane fermentation. This biotechnological process will contribute to the removal of pollutants from sewage. At the same time, biofuel and biofertilizer are also produced. Therefore, research on methane fermentation of cannery effluents to obtain biogas (alternative biofuel) and digestate (plant growth stimulator) is relevant. The purpose of the work is to study the methane fermentation of cannery effluents with the production of biogas and digestate. The work's task is to study the process of methane fermentation of cannery effluents, determine the intensity of gas generation, study the stimulating effect of digestate on plant seeds. The initial COD of the effluents is 4200 mg O2/dm3, pH 6,8. The research was carried out in a periodic regime, the loading dose was 30 %. Methane fermentation caused a high efficiency of wastewater treatment. The final value of the COD of the effluents was 500 mg O2/dm3. The cleaning efficiency is 88,1 %. The intensity of biogas release was high. Recorded biogas formation of 4 dm3 from 1 dm3 of wastewater. The amount of biogas in terms of the amount of initial pollution: 0,95 dm3/g of CODstart. The amount of biogas in terms of the amount of fermented pollution: 1,08 dm3/g of CODferm. Biogas had a high methane content – 65 – 68 %. Such biogas is used as an alternative biofuel. There is a clear classical interdependence between the reduction of sewage pollution and the release of biogas. Digestate is a valuable fertilizer and seed biostimulator. When seeds were treated with a digestate solution, the growth of roots (by 20 – 27 %), stems (by 21 – 30 %) was accelerated. Germination energy increased by 24,8 % compared to the control experiment.

Консервні підприємства є потужним джерелом стічних вод. Стічні води утворюються на різних стадіях технологічного процесу та забруднені вуглеводами, білками, жирами тощо. Часто такі стічні води не очищають або скидають у природні водойми неповністю очищеними. Доцільним є використання метанової ферментації. Такий біотехнологічний процес сприятиме вилученню забруднень із стоків. Також при цьому утворюються біопаливо та біодобриво. Тому актуальним є дослідження метанової ферментації стоків консервних заводів для отримання біогазу (альтернативне біопаливо) та дигестату (стимулятор росту рослин). Мета роботи – дослідження метанової ферментації стоків консервних виробництв з отриманням біогазу та дигестату. Завданням роботи є дослідження процесу метанової ферментації стоків консервних заводів, визначення інтенсивності газогенерації, дослідження стимулювальної дії дигестату на насіння рослин. Початкове ХСК стоків 4200 мг О2/дм3, рН 6,8. Дослідження проводили у періодичному режимі, доза завантаження – 30 %. Метанова ферментація зумовила високу ефективність очищення стоків. Кінцеве значення ХСК стоків становило 500 мг О2/дм3. Ефективність очищення – 88,1 %. Інтенсивність виділення біогазу була високою. Зафіксоване утворення біогазу 4 дм3 з 1 дм3 стічної води. Кількість біогазу у перерахунку на кількість початкових забруднень: 0,95 дм3/г ХСКпоч.. Кількість біогазу у перерахунку на кількість зброджених забруднень: 1,08 дм3/г ХСКзброд.. Біогаз мав високий вміст метану – 65 – 68 %. Такий біогаз використовують як альтернативне біопаливо. Прослідковується чітка класична взаємозалежність між зменшенням вмісту забруднень стоків та виділенням біогазу. Дигестат є цінним добривом і біостимулятором насіння. При обробці насіння розчином дигестату відбувався прискорений ріст корінців (на 20 – 27 %), стебел (на 21 – 30 %). Енергія проростання збільшилась на 24,8 % відносно контрольного досліду.
Keywords: кафедра технології оздоровчих продуктів; кафедра екології та екоменеджменту; biogas; canning industry; digestate; environment protection; methane fermentation; wastewater; біогаз; біодобриво; дигестат; консервна промисловість; метанова ферментація; охорона довкілля; стічні води; стічні води